Effective Strategies for Extracurricular Management to Improve Children's Achievement and Character in Ra Babul Huda Duko Rubaru Sumenep - Ulfah Ulfah; Nurul Falah; Lailatu Rohmah; Erni Munastiwi (Edumaspul: Jurnal Pendidikan, 2024)
Extracurricular management has an important role in supporting the development of students' character, skills, and achievements outside of formal learning. This study aims to identify effective strategies in extracurricular management through careful planning, structured implementation, and continuous supervision and evaluation. The proposed strategy includes the provision of adequate facilities and infrastructure, efficient management of funds, and flexible scheduling so as not to interfere with academic activities. Solutions to overcome challenges in the implementation of extracurricular activities include collaboration with external parties and increasing the competence of coaches. The results of the study show that effective management is able to improve student discipline, cooperation, and independence, as well as strengthen social and emotional skills. Thus, extracurricular activities make a significant contribution in preparing students to face future challenges.